Gut Microbiota Signatures in Tumor, Para-Cancerous, Normal Mucosa, and Feces in Colorectal Cancer Patients - Li, Yanmin; Cao, Hong; Fei, Bojian; Gao, Qizhong; Yi, Wanya; Han, Weifeng; Bao, Chuanqing; Xu, Jianmin; Zhao, Wei; Zhang, Feng (Frontiers in Cell and Developmental Biology, 2022)
Background: Association studies have linked microbiome alterations with colorectal cancer (CRC). However, differences in tumor, para-cancerous, normal mucosal, and fecal microbiota remain to be strengthened. Methods: We performed a study on the ecologically rich and taxonomically diverse of gut microbiota using three types of colorectal mucosa (tumor mucosa, para-cancerous mucosa, normal mucosa) and feces from 98 CRC patients. Additionally, we profiled the microbiota in the fecal occult blood test (FOBT) positive and negative groups at different sampling sites. Results: We found striking variations between tumor mucosal microbiota and normal mucosal microbiota. However, there was no significant difference between tumor and para-cancerous mucosal microbiota, as well as between para-cancerous and normal mucosal microbiota, revealing that the para-cancerous mucosal microbiota was a transitional state between the tumor and normal mucosal microbiota. And the substantial shifts in the fecal microbiota compared to mucosal microbiota indicated the risk of using fecal microbiota to define mucosal microbiota. A strong correlation between FOBT positive and Fusobacterium was discovered, indicating this adherent-invasive genus was closely related to intestinal bleeding. Furthermore, we identified six key genera, including Fusobacterium, Gemella, Campylobacter, Peptostreptococcus, Alloprevotella, and Parvimonas, which appear to be consistently over-represented in tumor mucosa compared to normal mucosa and/or in mucosa compared to feces. Conclusion: Compositional alterations in the microbiota existed in three types of colorectal mucosa and feces in CRC patients. Six key genera may contribute to the topographic variances in the microbiota of tumor-bearing colorectum.